The Role and Existence of Land Statement in Land Rights Applications and Their Problems - Verawati Gunawan,; Tejo, Eko Susanto; Lucky Nurlita Sari,; Riris Risnayanti Rahmat,; Kania Juliawati,; Mega Rahayu,; Andrian Yogapranatha,; Haspada, Deny; Asril, Juli (International Journal of Scientific Research and Management (IJSRM), 2025)
Land is an important need for human life, because land is a source to meet the needs of people’s lives and is a source of gifts from God Almighty. The increasingly limited amount of land has an impact on increasing land problems or disputes that occur, including land that has been registered with the National Land Agency and has been certified. Example of a case studied is the falsification of a land statement by Atang for land belonging to his late parents which has been sold and has been certified in the names of David Gunawan, Tony Tjahjadi, and Rina Gunawan.This study uses a normative legal approach with analytical descriptive research specifications. Analysis of the data used in this study is qualitative normative. The data collection techniques used in this research is documentation studies.The results of the study concluded that land statement are no longer a mandatory requirement and are no longer needed in the process of applying for land rights registration, but this is not stated explicitly. The Village Office itself has a very important role in issuing various types of letters related to land rights ownership and is the responsibility of a Village Head. The author can provide suggestions: first, the Government should review the regulations that emphasize the elimination of land statement requirements in applications for land rights registration. Second, the Village Office and Village Head must always be more careful in issuing letters, especially letters of information relating to land ownership, so as not to cause new problems.